The Role of The Government In Improving The Quality of Education - Taufiq, Muhammad; Nashihah, Durratun (Department of Public Administration, 2023)
Governments have the responsibility to manage resources, design policies, and ensure equitable access to education. Participatory decisions and partnerships with various parties are also important aspects of this effort. With an effective role, the government can form an education system that is more inclusive, equitable, and relevant to the needs of the community, which in turn will have a positive impact on the development of future generations and the growth of the country as a whole. The purpose of this study is to describe and see the importance of improving the quality of education through the education administration system to be implemented as one of the benchmarks for education quality. The method used in this study uses a bibliometric approach with network analysis techniques that can describe the relationship of keywords with the main focus of the study. The results showed that the role of the government in improving the quality of education is a key factor in the formation of a quality education system. (1) Policy Formulation. Local governments have the authority to design education policies that suit the needs and characteristics of their region. This includes the development of local curricula, special education programs, and education-related regulations. (2) Provision of Access to Education. Local governments must ensure that all citizens in their areas have equal access to education.